The influence of pre-university education resources on school dropout and the unemployment rate in Romania is significant? - Marian Zaharia (Journal of Research and Innovation for Sustainable Society)
In Romania, especially at county level, school dropout rate in primary and secondary education, school dropout rate in high school and professional education, as well as unemployment rate, differ significantly from one county to another, the values being in some cases quite increase. Starting from these findings, the paper predicts the results of the comparative analysis of the evolution and transformations recorded by the educational infrastructure, and students per teacher in pre-university education, parallel to the school dropout rate and unemployment rate in 2022 versus 2012. The obtained results highlight the fact that the educational infrastructure and students per teacher in pre-university education do not have a significant influence on the school dropout rate and unemployment rate, the decrease being mainly the result of the standard of living and economic and social development at the local and county level.